2019
DOI: 10.3329/bjms.v19i1.43871
|View full text |Cite
|
Sign up to set email alerts
|

Prospects and Challenges of Precision Medicine in Lower- and Middle-Income Countries: A Brief Overview

Abstract: The trend of NCDs in most LMIC countries is slowly but gradually follows that of in the developed countries. There are four significant diseases reported by WHO, which are equally common, such as CVDs, diabetes, cancer, and chronic respiratory disease that causes widespread early death & morbidity. Indeed, it incurs an overwhelming financial burden to most countries in the world. The rise of drug-resistant microbes is another major problem. To overcome this issue, precision medicine (PM) comes into play wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 100 publications
0
5
0
Order By: Relevance
“…The study revealed that there is much room for improvement on the levels of knowledge, and is possibly an indicator that precision medicine in low and middle income countries are very much at its infancy ( Haque et al, 2020 ). Similar to the findings of this study, where pharmacists had good perceptions and were willing to pursue precision medicine (albeit in moderation), past research inferred that the idea of precision medicine, as well as pharmacogenomics, had been well received among primary care providers including general practitioners and pharmacists ( Luke et al, 2021 ; Surofchy et al, 2021 ; Gammal et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The study revealed that there is much room for improvement on the levels of knowledge, and is possibly an indicator that precision medicine in low and middle income countries are very much at its infancy ( Haque et al, 2020 ). Similar to the findings of this study, where pharmacists had good perceptions and were willing to pursue precision medicine (albeit in moderation), past research inferred that the idea of precision medicine, as well as pharmacogenomics, had been well received among primary care providers including general practitioners and pharmacists ( Luke et al, 2021 ; Surofchy et al, 2021 ; Gammal et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, with the epidemiological changes in these regions (cancer, traffic accidents, etc. ), unmet surgical burdens have become a major problem of morbidity and mortality 9,11,24 . The region with the gratest unmet surgical burden per 100.000 population is Sub-Saharan Africa 11 .…”
Section: What Is Global Surgery?mentioning
confidence: 99%
“…According to the U.S. National Library of Medicine, "Precision Medicine" is an emerging approach that considers individual differences such as genes, environment, and lifestyle for preventing and treating particular diseases [4], [12]. Furthermore, the institute of US National Cancer defines Precision Medicine as "a form of medicine that uses information about a person's genes, proteins, and environment to prevent, diagnose, and treat disease" [13]. Moreover, the approach of PM is the category of medical sciences that aims to predict the possibility of developing a disease, achieve a precise diagnosis, and optimize the best performance of treatment for a particular patient [14].…”
Section: Precision Medicinementioning
confidence: 99%